Jumlah Staphylococcus aureus dan kandungan nutrien susu akibat dipping puting menggunakan ekstrak daun belimbing wuluh (Averrhoa bilimbi Linn) pada sapi perah penderita mastitis subklinis - Patricia Romintan Aprilia; Sri Agus Bambang Santoso; Dian Wahyu Harjanti (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2016)
The aim of the experiment was to examine the influence of Averrhoa bilimbi leaves extract as an antiseptic for teat dipping in dairy cattle on the number of Staphylococcus aureus and milk nutrients. A total of 16 subclinical mastitic cows were used in a completely randomized Split in Time Design with 4 treatments and 4 replications. Teat dipping was conducted everyday after morning and evening milking for 9 days. The main plot was the different antiseptic: antiseptic solution containing 1%, 3% and 5% of Averrhoa bilimbi leaves extract (T1, T3 and T5 respectively) and povidone iodine (K+). The sub plot was the duration of teat dipping, in which the milk samples were taken at before treatment (H0) and 3 day, 6 day and 9 day of the treatment (H3, H6 and H9, respectively). The result showed no interaction between the different antiseptic and the duration of teat dipping. The number of Staphylococcus aureus in milk was reduced significantly (P<0.01) from H0 (5.26x103 CFU/ml) to H9 (0.09x103 CFU/ml). Moreover, the contents of protein, lactose and fat were increased significantly (P<0.01) with teat dipping treatment for 9 days. In conclusion, Averrhoa bilimbi leaves extract could be used as a natural teat dip antiseptic to prevent Staphylococcus aureus infection and to ensure a better milk quality. Keywords: Averrhoa bilimbi leaves, antiseptic, Staphylococcus aureus, milk nutrients